Analisis Gangguan Identitas Disosiatif Malingering oleh Aaron Stampler dalam Film Primal Fear oleh Gregory Hoblit (1996) - Salem, Claudio; Wantasen, Isnawati Lydia; Wallidaeny, Alwin Firdaus (Linguistika Kultura, 2025)
This article discusses about the characteristics of malingering dissociative identity disorder by Aaron Stampler in the film Primal Fear (1996). In order to analyze the data, the writer uses qualitative descriptive method and intrinsic and extrinsic approach. The writer uses psychological approach from Wellek and Werren theory and the characteristics of DID by using the theory of Halgin and Whitbourne (2010), and Malingering by using the theory of Rogers (2008) and the depiction of Aaron Stampler’s DID and describe his true personality by using theory of character by Boogs and Petrie (2008). The result of this research shows that Aaron Stampler malingered the characteristics of DID. The writer found that there are 5 characteristics of DID malingered by Aaron Stampler consisting of amnesia, depersonalization, derealization, identity confusion and identity alteration. Based on character analysis, Aaron's malingering DID is depicted through his appearance, dialogue, his external actions and the reactions of other characters in the film.